Comparison of Buccal Midazolam with Rectal Diazepam in the treatment of prolonged seizures in children (Northern International Medical College Journal, 2022)
Background : Seizure is common neurological disorder in children. It is one of the common causes of referral of child to hospital and often requires emergency intervention. Rectal diazepam is the established first line drug for this purpose, but seizure recurrence and respiratory depression are the two major side effects. Midazolam is a water-soluble benzodiazepine with anticonvulsive activity at physiologic PH, which facilitates its effects on brain tissue. Midazolam is also easy to use, and no adverse events were reported in relation to the route of administration.Objectives : To compare the efficacy and safety of buccal midazolam with rectal diazepam in the treatment of prolonged seizures in children.Methodology : This prospective randomized study was conducted in the Department of pediatrics, Sir Salimullah Medical College (SSMC) and Mitford Hospital, from March 2018 to December 2018.Fifty (50) patients aged 3 months to12 months who were convulsing and experiencing prolonged seizure (lasted >5 minutes) were included. Patients was randomly assigned to one of the two treatment arms: rectal diazepam and buccal midazolam. Primary and secondary outcome was compared between 2 treatment arms. Primary outcome was: 1. cessation of visible seizure activity within 10 minutes. 2. without recurrence of seizure in the subsequent hour. Secondary outcome included: 1. proportion with cessation of convulsion and exact time needed for cessation of convulsion within 10 minutes2. proportion of seizure recurrence in the sub sequent hours and within 24 hours after initial control and exact time of recurrence within the respective period. Also the safety and adverse effects were also compared.Results : The two groups did not differ significantly in sex, age, type of seizures, temperature, and baseline RBS, respiratory rate and blood pressure. Comparing the 2-treatment group, 13 (52%) patient experienced treatment failure who received rectal diazepam compared with 7 (28%) who received buccal midazolam (P>0 .05). For initial cessation of seizures, 18 (72%) seizures terminated within 10 minutes in the diazepam group compared with 19 (76%) in the midazolam and mean time to cessation of the seizure was 4.02±1.03 minutes and 4.4 ± 1.09 minutes respectively (p>0.05). Among the 18 children in whom seizure was initially controlled within 10 minutes by rectal diazepam, 6 (33.33%) of them experienced a seizure recurrence in the subsequent hour compared with 1 (5.26%) of 19 children in the buccal midazolam group (P